2022
DOI: 10.3389/fcell.2022.847859
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Attenuates Brain Damage and Neuroinflammation Following Experimental Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is still a major public health problem worldwide, and the research of neuroprotective drugs has encountered great difficulties. Whole body vibration (WBV) is a safe and powerful rehabilitative intervention in various clinical settings, but its effect on neurological diseases is not well documented. In this study, we investigated the effects of WBV pretreatment on brain damage following experimental TBI mimicked by controlled cortical impact (CCI) in mice. C57BL/6 J male mice were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the current experiment, two weeks intervention with low intensity (frequency of 30 Hz, amplitude of 50–200 μm) was applied to investigate brain markers related to neuroinflammation and neurogenesis. These two weeks of WBV can be considered as a relatively short duration of intervention compared to other studies with similar brain related subjects (4–12 weeks WBV) ( Huang et al, 2018 ; Raval et al, 2018 ; Cariati et al, 2021 ; Peng et al, 2021 ; Chen et al, 2022 ). Beneficial effects of relatively short-term (11 days) exercise intervention were demonstrated on mood and BDNF regulation ( Tomiga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the current experiment, two weeks intervention with low intensity (frequency of 30 Hz, amplitude of 50–200 μm) was applied to investigate brain markers related to neuroinflammation and neurogenesis. These two weeks of WBV can be considered as a relatively short duration of intervention compared to other studies with similar brain related subjects (4–12 weeks WBV) ( Huang et al, 2018 ; Raval et al, 2018 ; Cariati et al, 2021 ; Peng et al, 2021 ; Chen et al, 2022 ). Beneficial effects of relatively short-term (11 days) exercise intervention were demonstrated on mood and BDNF regulation ( Tomiga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, neurogenesis (based on DCX-immunostaining) seemed to be impaired in the Dentate gyrus by surgery. Although both active ( Seo et al, 2019 ; Mee-inta and Zhao, 2019 ) and passive exercises ( Peng et al, 2021 ; Chen et al, 2022 ) are associated with anti-inflammatory effects, neither intervention alleviated the surgery-induced neuroinflammation. However, WBV seemed to prevent the decline in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a recent paper confirmed that WBV attenuated traumatic brain injury-related damage through the regulation of neuroinflammation [ 91 ]. Whether this is also true for PD should be examined in either research on animals or humans.…”
Section: Discussionmentioning
confidence: 99%